2014
DOI: 10.1128/iai.00084-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Diguanylate Cyclase and Its Role in Porphyromonas gingivalis Virulence

Abstract: Porphyromonas gingivalis is a Gram-negative obligate anaerobic bacterium and is considered a keystone pathogen in the initiation of periodontitis, one of the most widespread infectious diseases. Bacterial bis-(3=-5=) cyclic GMP (cyclic di-GMP [c-di-GMP]) serves as a second messenger and is involved in modulating virulence factors in numerous bacteria. However, the role of this second messenger has not been investigated in P. gingivalis, mainly due to a lack of an annotation regarding diguanylate cyclases (DGCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…How- ever, the invasive activities varied between vesicles derived from 33277 and W83, which is consistent with the invasive activities observed in their originating cells (Wayakanon et al 2013). Since FimA was far more abundant in 33277 vesicles than in W83 vesicles, we speculated that a decreased invasive activity would be found in vesicles from the fimA mutant, as we showed previously that the fimA mutant lost 90% of its invasive activity into HGFs (Chaudhuri et al 2014). Surprisingly, vesicles from this mutant showed a similar invasive activity as 33277, while vesicles from the fimR mutant showed a significantly decreased invasive activity, due to reduced expression of the fim locus that encodes minor components (FimC, FimD, and FimE) of long fimbriae.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…How- ever, the invasive activities varied between vesicles derived from 33277 and W83, which is consistent with the invasive activities observed in their originating cells (Wayakanon et al 2013). Since FimA was far more abundant in 33277 vesicles than in W83 vesicles, we speculated that a decreased invasive activity would be found in vesicles from the fimA mutant, as we showed previously that the fimA mutant lost 90% of its invasive activity into HGFs (Chaudhuri et al 2014). Surprisingly, vesicles from this mutant showed a similar invasive activity as 33277, while vesicles from the fimR mutant showed a significantly decreased invasive activity, due to reduced expression of the fim locus that encodes minor components (FimC, FimD, and FimE) of long fimbriae.…”
Section: Discussionmentioning
confidence: 76%
“…Transmission electron microscopy of P. gingivalis vesicles was conducted as described previously (Chaudhuri S, et al. ). Porphyromonas gingivalis vesicles (0.5 ng) were suspended in 25 μ L ddH 2 O and applied to a Formvar‐coated copper grid (200 mesh, Electron microscopy Sciences, Hatfield, PA) for 1 min and were air‐dried.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The innate immune system of the host responds to decrease inflammation by activating mechanisms including the mononuclear/macrophage system. Increased levels of inflammatory factors and release of matrix metalloproteinases may cause irreversible decomposition of collagen fibers in the periodontium, resulting in periodontal bone loss and organizational damage (29,30). Ogawa et al (31) demonstrated that the detection rate of P. gingivalis FimA-specific antibody-expressing cells increased with the development of periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Information on cyclic dinucleotides in periodontal disease pathogenesis is limited and the presence and regulatory functions of the molecules in oral bacteria remain to be fully characterized. The presence of cdi-GMP, or its binding proteins, has been demonstrated in some periodontitis-associated bacteria, including Porphyromonas gingivalis, Treponema denticola, and Selenomonas noxia [6][7][8][9]. In addition, these secondary signaling molecules have been found to regulate the oxidative response, extracellular polysaccharide matrix production, and biofilm formation of cariogenic Streptococcus mutans [10,11].…”
Section: Introductionmentioning
confidence: 99%